1991
DOI: 10.1128/mcb.11.12.5885
|View full text |Cite
|
Sign up to set email alerts
|

A position-dependent silencer plays a major role in repressing alpha-fetoprotein expression in human hepatoma.

Abstract: A large percentage of human hepatomas produce a-fetoprotein (AFP), but the levels of AFP expression vary greatly among hepatomas. To understand the molecular basis for this variation, we analyzed tanscriptional regulatory activities associated with the 5'-flanking region of the AFP gene in two human hepatoma cell lines, HuH-7 and huH-1/cl-2, which produce a high and a low level of AFP, respectively. We found that the low level of AFP production in huH-1/cl-2 is due to the action of at least two silencer region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 35 publications
1
87
2
Order By: Relevance
“…However, relatively low frequency of AFP expression in human HCC may hamper the clinical application. Although serum AFP was elevated in 70% of HCC patients (Nakabayashi et al, 1991), AFP transcripts were not frequently detected with Northern blot analysis as shown in the present study. Di Biscegile et al (1986) reported that nine out of 10 HCC patients showed elevated serum AFP values, but only two out of the 10 HCC specimens were positive for the mRNA with Northern blot analysis.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…However, relatively low frequency of AFP expression in human HCC may hamper the clinical application. Although serum AFP was elevated in 70% of HCC patients (Nakabayashi et al, 1991), AFP transcripts were not frequently detected with Northern blot analysis as shown in the present study. Di Biscegile et al (1986) reported that nine out of 10 HCC patients showed elevated serum AFP values, but only two out of the 10 HCC specimens were positive for the mRNA with Northern blot analysis.…”
Section: Discussioncontrasting
confidence: 62%
“…MK2.3kb-luc DNA was digested with XhoI/Eco47III to produce the 609-bp fragment-linked firefly luciferase genes (MK0.6-luc). The AFP promoter region (AFP0.2, 212-bp SacI/HindIII fragment) and the enhancer (934-bp SwaI/ EcoRI fragment)-linked AFP promoter region (AFPEn0.2) were prepared from pAF5.1-CAT (Nakabayashi et al, 1991), and they were subcloned into pGL2-basic vector (AFP0.2-luc, AFPEn0.2-luc). The transcriptional activity was measured with the dual luciferase reporter assay system (Promega).…”
Section: Dual Luciferase Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…13 To overcome this obstacle, we developed an OV that specifically targeted hepatocellular carcinoma (HCC) cells and improved the safety by replacing the E1A promoter of the ZD55 vector with a liver-cancer specific a-Fetoprotein (AFP) promoter, which was reported to be preferentially expressed in over 70% of human liver cancer patients through transcriptional activation. 14,15 We named this new OV as Ad Á AFP Á D55. In this work, we further inserted IL-24 and TRAIL genes individually into Ad Á AFP Á D55 to generate Ad Á AFP Á D55-IL-24 and Ad Á AFP Á D55-TRAIL, and then evaluated the combined antitumor effects of treatment with these two new oncolytic Ads in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%